2021
DOI: 10.1136/bmjopen-2020-045880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uncontrolled hypertension in people with comorbidities in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: BackgroundThe burden of uncontrolled hypertension in sub-Saharan Africa (SSA) is high and hypertension is known to coexist with other chronic diseases such as kidney disease, diabetes among others. This is the first systematic review and meta-analysis to determine the burden of uncontrolled hypertension among patients with comorbidities in SSA.MethodsA comprehensive search was conducted on MEDLINE, Excerpta Medica Database (Embase) and Web of Science to identify all relevant articles published between 1 Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
2
12
2
Order By: Relevance
“…The pooled prevalence of suboptimal blood control in diabetes patients among 21 studies in SSA was 69.8% (95% CI : 63.43, 76.25%), which is in line with the study among diabetes patients in 11 sub-Saharan African countries (74.5%) [ 63 ]. However, due to the difference in blood pressure cut point used to diagnose suboptimal BP control by these studies, subgroup analysis was done by BP cut point.…”
Section: Discussionsupporting
confidence: 81%
“…The pooled prevalence of suboptimal blood control in diabetes patients among 21 studies in SSA was 69.8% (95% CI : 63.43, 76.25%), which is in line with the study among diabetes patients in 11 sub-Saharan African countries (74.5%) [ 63 ]. However, due to the difference in blood pressure cut point used to diagnose suboptimal BP control by these studies, subgroup analysis was done by BP cut point.…”
Section: Discussionsupporting
confidence: 81%
“…This is lower than the findings from other previous studies conducted in Tanzania, which reported 66% prevalence in Dar es Salaam and 84.5% in Mwanza 42 43. Our study findings are also lower when compared with systematic reviews and meta-analyses of uncontrolled hypertension among patients with comorbidities in SSA which reported a prevalence ranging between 69.9% and 78.6% among patients with comorbidities and 79.8% among patients with CKD in China 19 20 25. These differences could be accounted by variations in the studied populations.…”
Section: Discussioncontrasting
confidence: 98%
“…The African region reported the highest prevalence of hypertension (46%) compared with other regions 18. The prevalence of uncontrolled hypertension among patients with comorbidities in SSA has been reported to be 78.6%, and it was 79.8% in a study conducted in China among patients with CKD 19 20. The prevalence of CKD in Tanzania is estimated to range between 25.7% and 45%, with the leading cause of CKD being hypertension 21–24.…”
Section: Introductionmentioning
confidence: 99%
“…Salt is a well-documented risk factor for hypertension, but not for diabetes [41]. However, hypertension and diabetes present together in a high proportion of patients [42][43][44]. Therefore, the analogy could also signify familiarity with the healthy eating advice provided to patients with diabetes in Sub-Saharan Africa, which typically includes salt-reduction to prevent or control comorbid hypertension [45,46].…”
Section: I) Depth Of Contentmentioning
confidence: 99%